Street Experience Jalan Braga : Memahami Pemenuhan Kebutuhan Pejalan Kaki melalui Media Google Street View - Pradharma, Brian Filbert; Alnindya, Diandri Taqia; Pourine, Bunga Aninditya Mayang; Ekomadyo, Agus Suharjono; Susanto, Vanessa (Jurnal Arsitektur ZONASI, 2021)
Abstract: The purpose of this study was to find out how pedestrian needs are met through visual elements of the streetscape to recognize the street experience offered by Braga Street, Bandung. Street is a place where people interact which shapes the aesthetic quality, economic activity, health and sustainability of society. There are 5 levels of needs for pedestrians or the hierarchy of walking needs, namely feasibility, accessibility, safety, comfort, and pleasurability. Braga Street itself has an active frontage form with wide building openings to increase the area's activity. As a heritage area, cultural heritage buildings on Braga Street have been preserved by making this area as tourist destination where the street is the main activities center. The method used is collecting image data of Braga Street via Google Street View and making a checklist of visual elements that can be applied from these aspects. From these findings, it can be concluded that all pedestrian needs based on the visual elements of the streetscape of Braga Street have been fulfilled, but the management still need to be improved to create a better quality of street experience for Braga Street.Keywords: street experience; walking needs; pedestrian; Google Street ViewAbstrak: Tujuan dari penelitian ini adalah mengetahui bagaimana kebutuhan pedestrian dipenuhi melalui elemen-elemen visual streetscape untuk mengenali street experience yang ditawarkan Jalan Braga, Bandung. Jalan merupakan tempat dimana orang-orang berinteraksi yang membentuk kualitas estetika, kegiatan ekonomi, kesehatan dan keberlanjutan masyarakat. Terdapat 5 kebutuhan pejalan kaki atau walking needs yaitu feasibility, accessibility, safety, comfort, dan pleasurability. Jalan Braga sendiri memiliki bentuk active frontage dengan bukaan-bukaan bangunan yang lebar untuk meningkatkan keaktifan kawasan. Sebagai kawasan heritage, bangunan-bangunan cagar budaya di Jalan Braga dilestarikan dengan menjadikan kawasan ini sebagai tempat wisata dengan jalan sebagai pusat aktivitas utama Metode yang digunakan adalah pengambilan data gambar Jalan Braga melalui Google Street View dan membuat checklist item elemen visual yang menjadi pengaplikasian dari aspek kebutuhan pejalan kaki. Dari temuan-temuan tersebut, dapat ditarik kesimpulan bahwa semua kebutuhan pejalan kaki berdasarkan elemen-elemen visual streetscape Jalan Braga sudah terpenuhi, namun pengelolaannya dapat ditingkatkan kembali untuk menciptakan kualitas street experience Jalan Braga yang lebih baik.Kata Kunci: street experience; walking needs; pedestrian; Google Street View